QUALITATIVE ASPECTS OF GROUNDWATER IN TUBULAR WELLS IN CAMPO GRANDE – MS - Cardoso, J. M.; Bega, J. M.M. [UNESP]; de Oliveira, J. N. [UNESP]; Américo-Pinheiro, J. H.P. (Universidade Estadual Paulista - Campus de Tupa, 2020)
This work aimed to evaluate the quality of groundwater granted in the municipality of Campo Grande-MS, more precisely the parameters: hydrogen potential, turbidity, nitrate, nitrite, sulfate and thermotolerant coliforms. For that, the IMASUL (Instituto de Meio Ambiente de Mato Grosso do Sul) System of Records and Strategic Information of the Environment was used as source of the data, through which the entire procedure for grant application and analysis is carried out. Interpolation maps were created using the Inverse Distance Weighting (IDW) method, which uses known values to estimate unknown values to better represent spatially the possible concentration of the analyzed parameters. Some parameters showed changes that varied according to the location of the wells, rural or urban, such as the concentration of nitrate in the water of six wells corresponding to levels above 10 mg/L. In general, according to CONAMA Resolution n° 396/2008, for the evaluated parameters, Campo Grande water is considered of good quality for recreational use and of relatively good quality for human consumption, as there are parameters in disagreement with the Consolidation Ordinance n° 5/2017.
ASPECTOS QUALITATIVOS DA ÁGUA SUBTERRÂNEA DE POÇOS TUBULARES EM CAMPO GRANDE – MS
Keywords: hydrogeology; urban pollution; water resources